Analisis Aset Pemerintah Daerah Kabupaten Tasikmalaya Tahun 2019-2020 - Rahma Awaliyah (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The balance sheet as one of the local government financial statements consisting of assets that describe the condition of economic wealth owned by the local government, but in the balance sheet of the local government of Tasikmalaya Regency there is a decrease in assets, namely current assets and other assets. The purpose of this study is to analyze assets on the balance sheet of the local government of Tasikmalaya Regency so that it can be seen how the financial condition of the Tasikmalaya Regency Government is, how is the ability of the Tasikmalaya Regency Government to fulfill its obligations, and the indicators behind the decline in assets by using financial ratios. which consists of the liquidity ratio and solvency ratio. The research method used in this research is descriptive qualitative method with data collection techniques using observation, interviews, and documentation. While the validity of the data is tested by using data triangulation. The results showed that the financial condition of the Tasikmalaya Regency Government was in prime condition and the Tasikamalaya Regency Regional Government was very good at fulfilling its obligations as seen from the results of the analysis of liquidity ratios and solvency ratios. The decline in asset value in 2020 at the Tasikamalaya Regency Government was influenced by a decrease in current assets due to a decrease in cash and a decrease in other assets due to asset write-offs.